Augmentation of optoelectronic properties via P3HT doping for low temperature processed perovskite solar cell - Mahmud, M.; Elumalai, Naveen Kumar; Upama, M.; Wang, D.; Wright, M.; Chan, K.; Xu, C.; Uddin, A. (2018)
© 2017 IEEE. Methyl Ammonium Lead Halide Perovskite solar have shown immense potential to be a 'Game Changer' in the photovoltaic industry. Major barriers to commercialization of Perovskite solar cells are poor device stability and high temperature requirement with TiO2 electron transport layer, widely used in efficient Perovskite devices. Apart from severe moisture sensitivity and thermal degradation, Perovskite layer can be decomposed due to the TBP additive incorporation with Li-TFSI dopant in most commonly used hole transport layers like Spiro OMeTAD and P3HT. Nearly 500° C sintering temperature requirement for Titania electron transport layer also impedes the Perovskite manufacturing in roll-to-roll process on flexible substrate which has a stringent processing condition of sub 150° C temperature. In this work, we have introduced F4TCNQ dopant to replace TBP and Li-TFSI in P3HT HTL in a low temperature (<150° C) solgel ZnO ETL processed Methyl Ammonium Lead Triiodide Perovskite solar cell. F4TCNQ doped P3HT HTL devices have shown over two times higher power conversion efficiency compared to pristine P3HT HTL devices. To comprehend the performance enhancement with F4TCNQ dopant in P3HT, we have examined the optical and electronic properties of both the pristine and F4TCNQ doped P3HT devices. Absorbance of Perovskite film lying underneath the undoped and the F4TCNQ doped P3HT film has been investigated to understand superior optical property of F4TCNQ incorporated film. Mott Schottky analysis has been conducted to enunciate the enhanced electronic property with F4TCNQ dopant in P3HT HTL compared to pristine P3HT.